Proceedings of the 3rd KOBI Congress, International and National Conferences (KOBICINC 2020) 2021
DOI: 10.2991/absr.k.210621.020
|View full text |Cite
|
Sign up to set email alerts
|

Abundance and Distribution Patterns of Megadrilli Earthworms at Different Altitude in Kabawetan Tea Plantation, Bengkulu

Abstract: Earthworms are an important component of natural and agricultural land ecosystems. The existence of earthworms in agricultural land can increase soil fertility and also support a sustainable agricultural system. This study aims to determine the abundance and distribution patterns of megadrilli earthworms in the Bengkulu Kabawetan Tea Plantation. Determination of the research location used the stratified sampling method which consisted of altitude strata, namely an altitude of 800, 900, and 1000 meters above se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 6 publications
0
1
0
2
Order By: Relevance
“…In this study, we investigated the prevalence of E. garfiai in different areas located below and above 900 m asl and the results showed a higher prevalence of E. garfiai in sampling areas located above 900 m asl. Altitude has frequently been used as a parameter for studying biodiversity richness and it was previously reported that earthworms' communities adapt well to different gradients of altitude, increasing in number and variety of population, probably due to lower anthropogenic influence and higher soil quality [48][49][50][51]. The presence of higher densities of intermediate hosts has already been linked to abundance of parasite communities [52]; therefore, we suggest that the higher prevalence of this parasite at higher altitudes could probably be connected to a higher presence of earthworms (Lumbricus spp.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we investigated the prevalence of E. garfiai in different areas located below and above 900 m asl and the results showed a higher prevalence of E. garfiai in sampling areas located above 900 m asl. Altitude has frequently been used as a parameter for studying biodiversity richness and it was previously reported that earthworms' communities adapt well to different gradients of altitude, increasing in number and variety of population, probably due to lower anthropogenic influence and higher soil quality [48][49][50][51]. The presence of higher densities of intermediate hosts has already been linked to abundance of parasite communities [52]; therefore, we suggest that the higher prevalence of this parasite at higher altitudes could probably be connected to a higher presence of earthworms (Lumbricus spp.…”
Section: Discussionmentioning
confidence: 99%
“…Cacing tanah dapat hidup di berbagai ekosistem terresterial, baik ekosistem alami seperti hutan hujan tropis, maupun ekosistem buatan, seperti lahan pertanian dan perkebunan (Darmi et al, 2021). Kehadiran cacing tanah pada suatu habitat sering tidak merata, tergantung pada faktor lingkungannya, seperti vegetasi, tekstur tanah, dan ketersedian makanannya (Maulida, 2015).…”
Section: Pendahuluanunclassified
“…Metode yang digunakan dalam koleksi cacing tanah, yaitu metode kuadrat (30 x 30 x 20 cm) dan metode hand sorting (Suin, 2012). Pada setiap lokasi dibuat line transect ukuran 100 m, dan disepanjang line transect dibuat plot ukuran 30 cm x 30 cm sebanyak 20 pengulangan dengan jarak 5 m antar plot (Darmi et al, 2021). Pada setiap kuadrat tanah digali dengan kedalaman 20 cm, kemudian diletakkan pada lembaran plastik berukuran 1 x 1 m, untuk menghitung dan mengamati cacing tanah dilakukan dengan metode hand sorting (sortir dengan tangan).…”
Section: Metodeunclassified